Caderno de receitas para espantar tristezas: o saber-fazer da comida tradicional do sertão seco e do sertão molhado norte de Minas Gerais - Guimarães, Thaynara Thaissa Dias (2022)
This thesis aimed to analyze the aspects that involve the production of traditional food from the dry and wet north-mineiro and what is the relationship between traditional food and the way of life of the sertanejo populations. It also sought to interpret and analyze, specifically, to analyze the influence of practices and knowledge associated with the territory of the populations of the dry and wet backlands in the formulation of the know-how of traditional food; how sertanejas and sertanejos experience the know-how of traditional food in the present and what is the social narrative of food and the relationship it constitutes between the dry and wet backlands. In order to develop this research, a methodology capable of involving the complexity and subjectivity existing between know-how and traditional food was needed, so I made use of the triangulation of qualitative methods: bibliographic research, documentary research and field trips. Field observations took place in open-air markets, traditional festivals and academic events that had the leading role of the populations studied and also in the communities visited. In total, 54 people participated in this research, of which 36 are allocated in 13 family nuclei. The observations obtained in the field constituted the categories of analysis of this research, since it was only after the field trips that it was possible to transform the native categories into analytical ones, in this way, memory and everyday life guided the theories used here, covering western philosophical theories and Amerindians, food anthropology, literature, phenomenology and territory. This research made it possible to understand that the territory is the place of knowledge of the sertanejo peoples of the dry and wet backlands, where authentic, plural food is established, which reverberates the history of its people. Traditional food in this research is a mediator and constituent of social life, it is formed in everyday life, it represents the vital force of tradition that moves in time and space through affection and sociability, transported between generations by a collective memory that is anchored in artifacts. knowledge and, therefore, does not exist apart from subjects. Tradition and food imbued with elementary gestures and attentive looks. A know-how that is never summarized, inventive, which is given by métis, composed of intelligence, practice, astuteness and creativity, whose routine of the look shapes the routine of the gesture. It has in childhood the depository center of knowledge. A childhood crossed by the temporality of waiting and patience and, therefore, subject to a reinvented and changing tradition, in a constant dialectic of old and new, but always recognized in ancestry.